“Ada Apa Dengan Gen Z” Studi Fenomenologi Generasi Net Di Tengah Dilematisasi Antara Gaya Hidup Dan Kearifan Lokal - Ni Made Prihanadi Dwi Surya Putri; I Putu Dharmawan Pradhana; Ketut Elly Sutrisni (Jurnal Manajerial, 2023)
Background – Generation Z is a generation that grows and develops in today's rapid technological developments. This also applies to Gen Z who are part of Balinese society and are very strong in cultural nuances and local wisdom. The tourism industry and modernity coexist with the strong culture that is the pulse of people's lives, creating an interesting phenomenon for the development of Generation Z in Bali. Especially those who work in various industries or as professionals. Aim – This research aims to find out how efforts are made by Generation Z in Bali in facing various pressures which are a dilemma between excellent performance in their place of work and the full contribution expected of them to cultural organizations amid conditions in Balinese society which are strong in implementing cultural activities based on local wisdom. Design/ Methodology/ Approach – This research uses a qualitative approach with phenomenological characteristics. Researchers try to explore the various activities of the sources and enter into the personal and social lives of the sources. The data validation technique uses the triangulation method, which consists of observation, interviews, and documentation. Informants were taken using a purposive sampling technique. The validity of the data is determined by source triangulation, technical triangulation, and time triangulation. Data analysis techniques are assisted by NVivo 12 Plus software. Findings – The strong traditions that Balinese people still maintain are also rooted in Generation Z. They feel that their obligations as krama (members) of Balinese society require them to remain active in various social activities. They will tend to try to manage their time and maintain their identity as part of Balinese society. If these conflicts are not resolved, they tend to choose to switch to jobs that can create flexibility in working so that they continue to carry out their activities as part of Balinese manners by becoming part of social organizations in Bali, in this case, Sekaa Teruna-Teruni and Banjar. Conclusion - There is harmony between Gen Z and the strong cultural roots and local wisdom in work rhythms and business organizations. Research Implication – This research shows that Generation Z cannot be fully identified as a generation that closely follows various developments and puts aside traditions that are considered ancient. In several areas that are thick with local wisdom and culture, Generation Z seems to be in harmony with the existing culture and forms an identity as Generation Z who can synergize modernity and tradition, thus creating a unique combination. However, sometimes there are various problems when they cannot synergize elements of the lifestyle and characteristics of the latest Gen Z with the local wisdom they adhere to. Limitations – This research uses phenomena taken from the perspective of a limited number of informants. The characteristics of local organizations and the company's organizational culture have not been studied further. Research with a greater number of sources and a deeper level of depth in the object being analyzed is necessary.